ANALISIS PENGARUH KINERJA KEUANGAN DENGAN METODE ECONOMIC VALUE ADDED (EVA) TERHADAP RETURN SAHAM PADA PERUSAHAAN PERTAMBANGAN DAN ENERGI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2008-2010 - B31106106, ANDY FRANSISCUS (Jurnal Manajemen Update, 2013)
The purpose of this research is to recognize the development of finance activity of mining and energy companies which measured by Economic Value Added (EVA) andMarket Value Added (MVA). And also to analyze the influence of EVA and MVA to return which will be received by shareholders of mining and energy companies which listed in Bursa Efek Indonesia (BEI) in 2008-2011 period which consist of 10 companies. The data collected in this research is pooling which is combination between time series consist of 4 time periods and cross section which consist of 10 companies. The amount of the samples in this reseach are 10 companies in 4 periods which will be chosen by purposive judgment sampling based on the purpose of the research, data availability, and trading condition in BEI. Data quantity of this research are 40. The analysis method used is double regression linier with SPSS program. Result of the research shows that EVA and MVA simultaneously affect return of the share from mining and energy company, however partially only MVA that will affect positively and significantly to the return of the share. This is due to the amount of MVA is considered represent performance of a share that the investor more concerned about MVA performance than EVA. The determination coefficient of R Square is 0,175 or 17,5%. This shows that the affect of EVA and MVA is considered small and assessment of this performance is not the main factor for the share price. Another cause which could be connected with the result above is the fact about the difficulty in calculating EVA and MVA. The amount of EVA and MVA is not stated in the fnancial report of the company. A lot of data is needed to calculate EVA, especially for the accounting adjustment and WACC from financial report or another resources. A the result of this difficulty, the share market subject face difficulty in making a decision based on EVA and MVA. Keywords: Economic Value Added (EVA), Market Value Added (MVA), and Return of Investment